O celach nauki organizacji i zarządzania - Jokiel, Grzegorz (About Purposes in Science of Organization and Management, 2006)
A report deals with purposes of organizing and management sciences. It presents genesis of academic management, characterizes differences between environmental sciences and the social ones (particularly organizing and management sciences), furthermore the problem of the possibility of the paradigm's creation for this particular branch of science has been considered. In this case the problem of the aims of the creation and development of the new conception of management has been described as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 57-63